2012
DOI: 10.3402/ijch.v71i0.18501
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rates of diabetes amongst status Aboriginal youth in Alberta, Canada

Abstract: ObjectivesTo track and compare trends in diabetes rates from 1995 to 2007 for Status Aboriginal and general population youth.Study designLongitudinal observational research study (quantitative) using provincial administrative data.MethodsDe-identified data was obtained from Alberta Health and Wellness administrative databases for Status Aboriginal (First Nations and Inuit people with Treaty status) and general population youth (<20 years). Diabetes cases were identified using the National Diabetes Surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…A similar increasing trend in the incidence of type 2 diabetes among children from 2006 to 2011 was reported in Manitoba, where 87% of children with diabetes had First Nations heritage. 5 The prevalence (0.27/100) and incidence (59/100 000 per year) of all types of diabetes in Aboriginal youth in Alberta in 2007 22 are similar to what we report in Ontario. Native American children in the United States, 2 Aboriginal children in Canada 4 and First Nations children in Manitoba 5 have a higher incidence of type 2 diabetes than children in the general population.…”
Section: Open Researchsupporting
confidence: 79%
“…A similar increasing trend in the incidence of type 2 diabetes among children from 2006 to 2011 was reported in Manitoba, where 87% of children with diabetes had First Nations heritage. 5 The prevalence (0.27/100) and incidence (59/100 000 per year) of all types of diabetes in Aboriginal youth in Alberta in 2007 22 are similar to what we report in Ontario. Native American children in the United States, 2 Aboriginal children in Canada 4 and First Nations children in Manitoba 5 have a higher incidence of type 2 diabetes than children in the general population.…”
Section: Open Researchsupporting
confidence: 79%
“…35 Annual incidence rates from 1994 to 2003 increased by 3.7% among white, 3.9% among black, and 9.6% among Hispanic children with insulin-treated, non–type 1 diabetes in Chicago 14 ; however, these case patients represent an unknown proportion of all case patients. Among aboriginal youth in Alberta, Canada, 12 a 14% average annual increase was reported in Chicago between 1995 and 2007 in youth younger than 20 years. Dabelea et al 7 showed an increase in prevalence of type 2 diabetes in Pima Indian youth aged 10 through 19 years in both sexes, with the highest prevalence in females.…”
Section: Discussionmentioning
confidence: 99%
“…Most have involved American Indians and Native Canadians and showed high prevalence. 7,12,13 Similarly, type 2 diabetes incidence rates rose among non-Hispanic black (hereafter called black), Hispanic, and white children with insulin-treated, non–type 1 diabetes from 1994 to 2003. 14 …”
mentioning
confidence: 99%
“…looked at the incidence of diabetes in Aboriginal youth <20 years of age in Alberta and reported an increasing trend from 1997 to 2005. [10]…”
Section: Introductionmentioning
confidence: 99%